2022
DOI: 10.1002/eap.2576
|View full text |Cite
|
Sign up to set email alerts
|

Turnover and nestedness drive plant diversity benefits of organic farming from local to landscape scales

Abstract: Biodiversity‐benefits of organic farming have mostly been documented at the field scale. However, these benefits from organic farming to species diversity may not propagate to larger scales because variation in the management of different crop types and seminatural habitats in conventional farms might allow species to cope with intensive crop management. We studied flowering plant communities using a spatially replicated design in different habitats (cereal, ley and seminatural grasslands) in organic and conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
6
1
Order By: Relevance
“…The high beta diversity but low gamma diversity for organic land management suggests that we could not scale up from changes in beta diversity to predict changes in gamma diversity, as suggested by theoretical predictions (Anderson et al, 2011). This contrasts with the findings of Carrié et al (2022), who found greater plant gamma diversity for organic than conventional farms, but no difference in field scale “intrahabitat” turnover.…”
Section: Discussioncontrasting
confidence: 99%
“…The high beta diversity but low gamma diversity for organic land management suggests that we could not scale up from changes in beta diversity to predict changes in gamma diversity, as suggested by theoretical predictions (Anderson et al, 2011). This contrasts with the findings of Carrié et al (2022), who found greater plant gamma diversity for organic than conventional farms, but no difference in field scale “intrahabitat” turnover.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study and these previous studies suggest that they rapidly increase after the transition and remain constant thereafter. This could be due to the exclusion of chemical pesticides on organic farms, such as herbicides and insecticides, which are major determinants of diversity in plants and spiders (Amano et al, 2011; Carrié et al, 2022; Jonason et al, 2011). In addition, small field sizes in Japan can allow plants and spiders to migrate from adjacent non‐crop habitats to rice fields soon after the transition to organic farming (Baba et al, 2018; Tsutsui et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study and these previous studies suggest that they rapidly increase after the transition and remain constant thereafter. This could be due to the exclusion of chemical pesticides on organic farms, such as herbicides and insecticides, which are major determinants of diversity in plants and spiders (Amano et al, 2011;Carrié et al, 2022;Jonason et al, 2011).…”
Section: F I G U R Ementioning
confidence: 99%
“…Although arable fields selects for weed species with high R score (fast growing) due to high disturbance frequencies and availability of nutrients compared to perennial crops such as leys (MacLaren et al, 2020), we were expecting plant communities in organic cereal fields to have relatively more species with slower life cycles due to lower disturbance frequency in organic fields, especially in case of reduced tillage (Halde et al, 2015). In another study we conducted in the same region (see design in Carrié et al, 2022), only 22% of organic farmers adopted reduced tillage practices, suggesting that similar R score of weed species in organic and conventional fields could be due to comparable soil disturbance frequency in the two systems. However, we found that the proportion of species with longer generation time in leys increased with increasing proportion of surrounding semi-natural grasslands.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…Jonason et al., 2011; Taylor & Morecroft, 2009), which could partly be explained by two kinds of factors affecting species probability to exhibit a delayed response to organic conversion. First, the quality of fields as habitat can improve incrementally after conversion, and this could differentially affect plant species depending on their sensitivity to local habitat characteristics (Carrié et al., 2022; Rundlöf et al., 2010). For example, pesticide and fertilizer residues can still affect plant communities in newly converted farms (Hyvönen, 2007) as microbial activities and mineralization processes, which contributes to break down these residues takes time to recover from intensive practices (Mäder et al., 2002).…”
Section: Introductionmentioning
confidence: 99%